(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Despite the fact that many societies have historically utilised herbs, Indians have a long,prosperous, and diversified cultural past of employing medicinal plants. The purpose of the current study,which is described in this article, is to evaluate the potential of herbal plants’ cultivation and theirtherapeutic value. The survey sought to determine both the total number of plants used in the preparationsand the presence of Roylea cinerea in these drugs. It was clear that up to 100 species, 80 of which arenative to the Morni Hills in Haryana, are employed in the creation of well-known herbal remedies.